2021
DOI: 10.1186/s13071-021-04991-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum biomarkers of inflammation in bovine besnoitiosis

Abstract: Background Acute and chronic besnoitiosis in extensive natural-service herds can have relevant effects in the health of bulls and negative consequences in their productive performance. Recent progress has been made in order to elucidate the pathogenesis of this disease. In this context, the study of biomarkers of inflammation in serum would contribute to gaining knowledge about the physiopathology of bovine besnoitiosis. Serological biomarkers could help in early diagnosis and prognosis, as ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Measurement of APP levels gives accurate and clear results in the diagnosis of inflammatory diseases in ruminants compared with hematological findings. It has been reported that it can be a helpful parameter in the diagnosis in the diseases such as neonatal diarrhea [25][26][27], omphalitis [28,29], pneumonia [30], ascaridiosis [31], besnoitiosis [32], Trypanosoma evansi [33], anaplasmosis [34][35][36], hypodermosis [37], in the bacterial and viral diseases such as brucellosis [38], tuberculosis [39], reticuloperitonitis traumatica [40,41], foot-and-mouth disease [42], as well as in fatty liver [43] including dystocia [44] and subclinical ketosis (Table 1) [45,46]. In addition, in another study conducted in cattle with endometritis, it has been reported that haptoglobin and TNF-α levels decreased significantly after the treatment compared to the pre-treatment values [47] and that progesterone-releasing intravaginal device (PRID) administration increases haptoglobin and ceruloplasmin levels, but decreases albumin levels in another study conducted by Kuru et al [48] in cattle.…”
Section: Some Acute Phase Proteins Important For Cattlementioning
confidence: 99%
“…Measurement of APP levels gives accurate and clear results in the diagnosis of inflammatory diseases in ruminants compared with hematological findings. It has been reported that it can be a helpful parameter in the diagnosis in the diseases such as neonatal diarrhea [25][26][27], omphalitis [28,29], pneumonia [30], ascaridiosis [31], besnoitiosis [32], Trypanosoma evansi [33], anaplasmosis [34][35][36], hypodermosis [37], in the bacterial and viral diseases such as brucellosis [38], tuberculosis [39], reticuloperitonitis traumatica [40,41], foot-and-mouth disease [42], as well as in fatty liver [43] including dystocia [44] and subclinical ketosis (Table 1) [45,46]. In addition, in another study conducted in cattle with endometritis, it has been reported that haptoglobin and TNF-α levels decreased significantly after the treatment compared to the pre-treatment values [47] and that progesterone-releasing intravaginal device (PRID) administration increases haptoglobin and ceruloplasmin levels, but decreases albumin levels in another study conducted by Kuru et al [48] in cattle.…”
Section: Some Acute Phase Proteins Important For Cattlementioning
confidence: 99%